Toward a holistic perspective of congruence research with the polynomial regression model. - Yao, Yongheng (Angus); Ma, Zhenzhong (Journal of Applied Psychology, 2023)
. We find that congruence researchers often fail to consider all the conditions required to test congruence effects. Our reanalysis of these studies shows that when all required conditions are used, the exact correspondence effect, sometimes also labeled as the exact match effect or the perfect match effect, is only supported in three studies. Caution is hence warranted both for citing these studies as evidence of congruence and for proposing practical implications based on the findings in these studies. A holistic perspective is then proposed in this study to facilitate the proper application of the PRRSA model to help congruence scholars develop stronger theories and enhance scientific rigor in congruence research. (PsycInfo Database Record (c) 2023 APA, all rights reserved).